Antibacterial activity test on ethanol extract fraction of Kirinyuh (Chromolaena odorata L.) leaves for multi-drug resistant organisms bacteria - Endang Sulistyarini Gultom; Tri Hartanti; Hasnaul Maritsa; Eko Prasetya (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
The resistance of pathogenic bacteria to antibiotics is increasing due to antibiotics with incorrect doses, wrong diagnostics, and the wrong target. Bacteria that have been resistant to several antibiotics are called multi-drug resistant organisms (MDRO) bacteria. Bacterial resistance to some antibiotics requires alternative herbal treatments, one of which is the Chromolaena odorata L. Research must therefore be conducted on the antibacterial activity of the ethanol extract fraction of C. odorata L. leaves for MDRO bacteria, such as Staphylococcus lugdunensis methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa extended-spectrum beta-lactamase (ESBL), and Klebsiella pneumoniae ESBL. This study aims to determine the antibacterial activity of the ethanol extract of Kirinyuh leaves (C. odorata L.) and the antibacterial activity of the fractionation against MDRO bacteria. Test results of kirinyuh leaf ethanol extract for S. lugdunensis MRSA, P. aeruginosa ESBL, and K. pneumoniae ESBL bacteria each resulted in an inhibition zone with an average diameter of 11.6 mm (strong), 11.5 mm (strong), and 11.13 mm (strong), respectively. Testing the antibacterial activity of the ethanol fraction against MDRO bacteria can show antibacterial activity against all tested bacteria, namely Fraction 5. The results of the antibacterial activity of fraction 5 against K. pneumoniae ESBL, P. aeruginosa ESBL, and S. lugdunensis MRSA bacteria with the formation of inhibition zones formed of 10.2 mm (strong), 8.8 mm (moderate), and 7.9 mm (moderate), respectively. The results of thin-layer chromatography showed that the secondary metabolites contained in the fifth fraction were terpenoids, steroids, and flavonoids.